2020
DOI: 10.1016/j.clinthera.2020.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-μg Dose of Dexmedetomidine in Combination With Intrathecal Bupivacaine on Spinal Anesthesia: A Systematic Review and Meta-analysis

Abstract: Purpose: Intrathecal dexmedetomidine (DEX) has been used to improve the quality and duration of spinal anesthesia. The aim of this meta-analysis is to evaluate whether intrathecal DEX could prolong the duration of sensory and motor block during spinal anesthesia. Methods: We searched PubMed, EMBASE, Web of Science, and the Cochrane Library for randomized controlled trials that investigated the facilitatory effects of intrathecal administration of DEX compared with those of a placebo on spinal anesthesia from i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
9
1
2
Order By: Relevance
“…DEX has been reported to be safe to use intrathecally. Previously published meta-analysis and reviews have shown that intrathecal infusions of DEX can shorten the onset time of spinal anesthesic as well as enhance and prolong their sensory and motor effects, and increasing the time to the need for pain rescue after spinal anesthesia [ 11 , 12 ]. Khosravi et al demonstrated that intrathecal DEX produced better outcomes in terms of analgesia, sedation, and hemodynamic parameters compared to intravenous DEX [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…DEX has been reported to be safe to use intrathecally. Previously published meta-analysis and reviews have shown that intrathecal infusions of DEX can shorten the onset time of spinal anesthesic as well as enhance and prolong their sensory and motor effects, and increasing the time to the need for pain rescue after spinal anesthesia [ 11 , 12 ]. Khosravi et al demonstrated that intrathecal DEX produced better outcomes in terms of analgesia, sedation, and hemodynamic parameters compared to intravenous DEX [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 The most representative intrathecal adjuvants in clinical practice for labor analgesia are opioids and a 2 -adrenergic receptor agonists. 19 In this study, compared with the use of 5 mg sufentanil intrathecally combined with 0.1% epidural ropivacaine þ 0.2 mg/mL sufentanil, the use of 5 mg Dex intrathecally combined with the epidural drugs described above offered similar pain relief during labor with less shivering and pruritus. Therefore, Dex is a good alternative in labor analgesia as an intrathecal drug combined with epidural analgesia.…”
Section: Discussionmentioning
confidence: 87%
“…15 Another study by Khan et al reported that the addition of Dexmedetomidine along with Bupivacaine is beneficial in terms of quicker onset and prolonged duration of analgesia. 16 However, these authors used 5µg Dexmedetomidine, and in the present study, we used 10µg Dexmedetomidine as an adjuvant. Other studies have also reported similar results.…”
Section: Discussionmentioning
confidence: 94%